2017
DOI: 10.4103/2277-9531.204749
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between media literacy and health literacy among pregnant women in health centers of Isfahan

Abstract: Background:The ability to access, analyze, evaluate, and convey information in various forms of media including print and nonprint requires media literacy, but the capacity to obtain, process, and understand basic information and services needed for appropriate decisions regarding health, considered an important element in a woman's ability to participate in health promotion and prevention activities for herself and her children, is needed to a level of health literacy. The purpose of this study was to determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 10 publications
1
19
0
Order By: Relevance
“…This lower HL status observed in pregnant women recipients of a conditional cash transfer programme is concerning and consistent with other studies (Lori, et al, 2015;Akbarinejad, Soleymani & Shahrzadi, 2017) observed that more than half of pregnant women analysed presented inadequate HL. Lori, et al (2015) indicated that pregnant women with low HL interpret the information received incorrectly, execute health skills incorrectly during prenatal care, and do not understand that health services may help them and their families.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…This lower HL status observed in pregnant women recipients of a conditional cash transfer programme is concerning and consistent with other studies (Lori, et al, 2015;Akbarinejad, Soleymani & Shahrzadi, 2017) observed that more than half of pregnant women analysed presented inadequate HL. Lori, et al (2015) indicated that pregnant women with low HL interpret the information received incorrectly, execute health skills incorrectly during prenatal care, and do not understand that health services may help them and their families.…”
Section: Discussionsupporting
confidence: 91%
“…Our study population presented lower results in all structural factors than the studies by Abel, et al (2015), Guo, et al (2018) and Quemelo, et al, (2017). This result may be explained by the lower level of education of pregnant women investigated, considering there is a direct relationship between HL and levels of education (Duggan, et al, 2014;Castro-Sánchez, et al, 2018;Akbarinejad, Soleymani & Shahrzadi, 2017). It is worth noting that, despite the impact of level of education on HL, improving this parameter alone is not enough to improve HL levels (Lupattelli, et al, 2014).…”
Section: Discussionmentioning
confidence: 51%
See 2 more Smart Citations
“…The test validity was confirmed by experts in the field of media, communication, and library. The reliability was calculated using the Cronbach α in the first to fifth dimensions, respectively, as 0.813, 0.899, 0.909, 0.926, 0.773, and totally, 0.971 (Akbarinejad, Soleymani, & Shahrzadi, 2017). The Persian version of the inventory was administered to the participants in this study, and its reliability was reported to be 0.95 using the Cronbach α coefficient.…”
Section: Phase 3: the Mixed Quantitative-qualitative Phasementioning
confidence: 99%